Reelin Improves Cognition and Extends the Lifespan of Mutant Ndel1 Mice with Postnatal CA1 Hippocampus Deterioration. (24th April 2020) - Kiroski, Ivana; Jiang, Yulan; Gavrilovici, Cezar; Gao, Fan; Lee, Sukyoung; Scantlebury, Morris H; Vandal, Milene; Park, Sang Ki; Tsai, Li-Huei; Teskey, G Campbell; Rho, Jong M; Nguyen, Minh Dang
Abstract: The glycoprotein Reelin maintains neuronal positioning and regulates neuronal plasticity in the adult brain. Reelin deficiency has been associated with neurological diseases. We recently showed that Reelin is depleted in mice with a targeted disruption of the Ndel1 gene in forebrain postnatal excitatory neurons (Ndel1 conditional knockout (CKO)). Ndel1 CKO mice exhibit fragmented microtubules in CA1 pyramidal neurons, profound deterioration of the CA1 hippocampus and a shortened lifespan ( 10 weeks). Here we report that Ndel1 CKO mice (of both sexes) experience spatial learning and memory deficits that are associated with deregulation of neuronal cell adhesion, plasticity and neurotransmission genes, as assessed by genome-wide transcriptome analysis of the hippocampus. Importantly, a single injection of Reelin protein in the hippocampus of Ndel1 CKO mice improves spatial learning and memory function and this is correlated with reduced intrinsic hyperexcitability of CA1 pyramidal neurons, and normalized gene deregulation in the hippocampus. Strikingly, when treated with Reelin, Ndel1 CKO animals that die from an epileptic phenotype, live twice as long as nontreated, or vehicle-treated CKO animals. Thus, Reelin confers striking beneficial effects in the CA1 hippocampus, and at both behavioral and organismal levels.